Effects of zinc supplementation in the prevention of respiratory tract infections and diarrheal disease in Colombian children: A 12-month randomised controlled trial (2020)
Background Among the preventive strategies for lowering the incidence of upper respiratory tract infections (URTI) and acute diarrhoea episodes, two of the most common diseases in children, zinc supplementation has received special interest. However, there is a need for additional studies that determine the preventive effects of different doses of zinc on URTI and diarrhoeal disease episodes in children. Methods In a randomised, triple-blind clinical trial, we evaluated the efficacy of 12 months of daily zinc supplementation in the incidence of URTI and acute diarrhoea in a population of healthy children aged between 6 and 12 months living in Bogota, Colombia. The outcomes analysed were incidence of URTI, acute diarrhoeal disease episodes, and side effects of the interventions. Results Between 2010 and 2013, a total of 355 children underwent randomisation, with 174 assigned to the zinc supplementation group and 181 to the control group. In the multivariate analyses, having been randomised to the non-supplemented control group (IRR 1.73, 95% CI 1.52–1.97, p < 0.001), and nursery attendance (IRR 1.41, 95% CI 1.07–1.87, p = 0.016) were independently linked to the number of URTI. Likewise, having been randomised to the non-supplemented group (IRR 1.43, 95% CI 1.20–1.71, p < 0.001), and lower socioeconomic status (IRR 1.86, 95% CI 1.11–3.13, p = 0.018) were independently associated to the number of diarrhoeal disease episodes. Conclusions Daily supplementation of 5 mg of zinc during 12 months significantly decreased the incidence of URTI and diarrhoeal disease episodes in a healthy population of children aged between 6 and 12 months.